Physicochemical properties of grass carp surimi as affected by pH and NaCl concentration during washing - Yudong Wang; Yuxin Tian; Jingwen Sun; Hong Yang (International Journal of Food Properties)
The objective of this study was to investigate the effects of various pHs and NaCl concentrations on physicochemical properties of surimi from grass carp during washing. Surimi protein recovery was higher with 0.25% and 0.5% NaCl at the pH 5 or 7 than that with other pHs and NaCl concentrations, while the highest recovery was obtained with 0.25% NaCl at the pH 7. It decreased protein recovery and salt-soluble protein of surimi as NaCl increased by more than 1.0% during washing. The water-soluble protein content was significantly higher at the pH 3 than at other pHs, while the SDS-PAGE of surimi protein exhibited intense sarcoplasmic protein bands at the pH 3. There were significantly fewer hydrophobic groups of actomyosin treated with 0.25% NaCl at the pH 5 or 7 than that with other pHs and NaCl concentrations in washing solution. The α-helix of actomyosin was increased with the increase of NaCl during washing. In general, the washing with 0.25%−0.5% NaCl at the pH 5–7 could significantly increase the yield of surimi from grass carp.